Testing and analysis of PVC liners under simulated grouting pressure. (1st January 2022) - Treitz, Josh; Lan, Haitao; Moore, Ian D.; Hoult, Neil A.
Highlights: Develop a test setup and procedure to undertake buckling experiments. Investigate the response of PVC liner under two different loading conditions. Compare the test measurements to theoretical values. Evaluate existing buckling and numerical models for predicting liner behaviour. Abstract: Sliplining is often selected for rehabilitation of deteriorated culverts and drainage structures, and involves placing a liner pipe within the deteriorated host pipe and filling the gap between the two with grout. However, currently the design of these liners to resist buckling during the critical grouting phase has not been evaluated experimentally. In addition to obtaining test data to evaluate existing buckling models, the tests permit assessment of the influence of buoyancy on liner stability and the influence of the size of the gap between the liner and host pipe. Therefore, this paper presents an experimental study undertaken after adapting an existing test cell. Two tests were conducted, one on a liner within the host pipe with their axes oriented vertically (so not affected by buoyancy) and another where pipe and liner axes were oriented horizontally and so subject to buoyancy. The liners were instrumented with distributed strain and displacement sensors, and subjected to simulated external grouting pressure using water pressure applied to a rubber bladder. Both liners first buckled under hydrostatic pressure and had greatly reduced incremental flexural stiffness until liner deformations brought it into contact with the test cell, at which point the liners took additional pressures until finally failing due to nonlinear buckling. Analytical and numerical estimates of the thrust forces in the liner and the hydrostatic buckling pressure were within 10% of the experimental values of maximum pressure on the liner (at the invert). However, it is not conservative to estimate the critical buckling pressure (the maximum or peak pressure before the pipe fails) using the existing buckling model. For the current tests, the hydrostatic and critical buckling pressures are almost independent of the distance between the axes of the liner and host pipe (i.e. where the contractor positions the liner within the post pipe)